Oral health of community‐dwelling older Australian men: the Concord Health and Ageing in Men Project (CHAMP). (30th October 2017) - Wright, FAC; Chu, SK‐Y; Milledge, KL; Valdez, E; Law, G; Hsu, B; Naganathan, V; Hirani, V; Blyth, FM; Le Couteur, DG; Harford, J; Waite, LM; et al.
Abstract: Background: The Concord Health and Ageing in Men Project (CHAMP) is a cohort study of the health of a representative sample of Australian men aged 70 years and older. The aim of this report is to describe the oral health of these men. Methods: Oral health was assessed when the men were all aged 78 years or older. Two calibrated examiners conducted a standardized intraoral assessment. Descriptive data were analysed by statistical association tests. Participants were excluded from the collection of some periodontal assessments if they had a medical contraindication. Results: Dental assessments of 614 participants revealed 90 (14.6%) were edentate. Men had a mean of 13.8 missing teeth and 10.3 filled teeth. Dentate participants had a mean of 1.1 teeth with active coronal decay. Those in the low‐income group had a higher rate of decayed teeth and lower rate of filled teeth. Thirty‐four participants (5.5%) had one or more dental implants, and 66.3% relied on substitute natural teeth for functional occlusion. Of those with full periodontal assessments; 90.9% had sites with pocket depths of 3 mm or more, 96.6% had sites with CAL of 5 mm or more, and 79.7% had three or more sites with GI scores of 2 or more. Conclusions: There was a high prevalence of periodontal diseases and restorative burden of dentitions, which suggests that greater attention needs to be given to prevention and health maintenance in older Australian men.